Covid-19 and sustainability narratives by IBEX-35 companies: Media representation in OECD countries - Castelló-Sirvent, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
COVID-l9 altered the relative importance of the sustainability of the business socio-technical system and the public sector. This article evaluates the change experienced in the media representation of the sustainability of IBEX-35 companies during two sub-periods. On the one hand, the two years before and after the declaration of the State of Alarm are analyzed. The search was carried out in Factiva® for all the countries of the Organization for Economic Co-operation and Development (OECD). The results suggest a change in the discourse of the largest Spanish companies by capitalization and a greater sectoral and institutional transversality